PARTNERSHIP AGREEMENT BY DOMINANT POSISSION UNDERTAKINGS: LEGAL PROTECTION OF MICRO, SMALL, AND MEDIUM-SIZED ENTERPRISES - Idha Racy Rosalia Hadi; Ria Setyawati (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Micro, Small, and Medium-sized Enterprise is the economic sector that can absorb the largest workforce in Indonesia. MSMEs must be empowered and developed to improve competitiveness. To develop businesses owned by large and small business actors, both of them make a partnership agreement. The purpose of this research is to develop and improve a mutually beneficial bargaining position for the parties in a partnership and to create a healthy business competition. It also aims to protect business actors in the perspective of business competition law so that in the market structure, there is no economic concentration by certain business groups and control of business partners. This research was conducted using a statute approach, an approach that uses legislation or regulations related to business competition law as well as those related to patterns of partnership between large business and MSME actors. Case approach was applied to conduct an analysis in accordance with the legal facts that exist to complement and describe the unfair business competition in the community. The results show there is an imbalance in the agreement that causes a loss to one of the parties. There are behaviors that can result in unfair business competition, such as abuse of bargaining position and unilateral price determination beyond normalcy. Indonesian laws regulate policies so that MSMEs can be treated fairly and receive legal protection in the event of abuse.